Autoethnography as a lighthouse : illuminating race, research, and the politics of schooling - Hancock, Stephen D.; Allen, Ayana; Lewis, Chance W. 1972- (Contemporary perspectives on access, equity, and achievement., 2015)
This work uses autoethnography as an enterprise to deconstruct barriers that support the invisibility of diverse epistemologies. The reality of invisibility and silence has plagued "unvalued others" in their attempt to make known the cultural significance found in the planning and execution of research. As a result, this book purposes to support the visibility and voice of marginalized scholars who conduct autoethnographic research from a racial, gendered, and critical theoretical framework. This work further supports authentic inquiry as it examines and reexamines culturally diverse epistemologies as a viable and valuable framework for conducting autoethnographic research. Specifically, this work highlights racialized epistemologies as an inescapable factor in auotethnographic research in the context of schools.